PERLINDUNGAN HAK ATAS TANAH ULAYAT MASYARAKAT ADAT GAYO DI KABUPATEN BENER MERIAH - Yowa Abardani Lauta; Syafruddin Kalo; Runtung Runtung; Edy Ikhsan (Universitas Sumatera Utara, 2016)
ABSTRACT The existence of ulayat rights (communal right of disposal or customary associative right) in Indonesia is recognized and respected as it is stipulated in the 1945 Constitution; this recognition is confirmed in Law No. 5/1960 on the Agrarian Basic Regulation. Ulayat rights actually still exists and is not contrary to the national interest and to any higher legal provisions. The Regulation of the Agrarian Minister No. 5/1999 on the Guidance for Settling the Problems of ulayat rights in the Adat Community orders the establishment of Regional Regulation on the recognition and protection for ulayat rights in each area in which it still exists. In reality, not all areas in Indonesia, including ulayat rights in the Gayo community in Bener Meriah District, has Regional Regulation for it. The result of the research showed that the existence of ulayat rights in the Gayo community still exists; it is indicated by the existence of the subject of ulayat rights, that is, ulayat rights object and the legal relationship between the subject and the object of ulayat rights. On the other hand, there are also some obstacles from its legal substance, legal structure, and legal culture in recognizing and protecting ulayat rights. Bener Meriah District Administration has established Majelis Adat (Adat Council) through Bener Meriah District Qanun No.4/2010 on Organizational Structure and Work Structure of the Secretariat of the Extraordinary Committee in Bener Meriah District and has published Bener Meriah Qanun No. 5/2011 on the Appointment of Animal Breeding Locations (peruweren) of Uber-Uber and Blang Paku in Bener Meriah. Keywords: Ulayat rights, Adat Gayo Community, Bener Meriah District